Effect of Cell Dose and Dose of Infectious Agent on Expression of Protection Against Listeria monocytogenes and Ectromelia Virus in Cell Transfer Models - Zinkernagel, R. M. (1975)
Two parameters (immune cell dose and dose of infectious agent) influencing the expression of protection by transferred immune spleen cells in Listeria monocytogenes and ectromelia virus infection in mice were investigated. First, when recipient mice were infected with a constant dose of ectromelia virus, a linear relationship between log(10) cells transferred and the protection obtained expressed as log(10) decrease in virus plaque-forming units per spleen was obtained, as has been described previously for the Listeria system. Second, the detectable protection was greatly affected by the number of viable bacteria or virus plaque-forming units relative to the number of transferred cells. An otherwise very effective number of transferred immune cells became ineffective when too great a dose of infection was used. Mouse strain differences could also have influenced the results. The impact of these and other parameters on the experimental outcome and its interpretation are discussed.